Reducing Food Insecurity through Personalized Interventions at the East Harlem Health Outreach Partnership - Alexandra Dembar; Anthony J Mell; Vicki Hsieh; Sandhya Chandrasekan; Robert Rifkin; David C Thomas; Yasmin S Meah (Journal of Student-Run Clinics, 2020)
Background: An individualized food insecurity protocol is defined as a comprehensive process of screening and set of interventions designed around the specific needs of an individual patient including but not limited to such factors as work schedule, place of living, and forms of identification. The aim of this project is to identify whether an individualized food insecurity protocol reduces food insecurity in the patients seen at the East Harlem Health Outreach Partnership (EHHOP), a student-run, attending-directed free clinic in East Harlem. Methods: Twenty-one patients who had screened positive for food insecurity in the past year were enrolled in the study. Pre- and post-intervention scores based on responses to a modified version of the United States Department of Agricultureâ€™s Six-Item Short Form of the Food Security Survey were recorded, compiled as aggregate data, and compared using the Wilcoxon signed-rank test. Results: The results of this study demonstrate that an individualized protocol was successful in reducing food insecurity (p = 0.005). However, for certain groups, the protocol was not as effective, including patients with poor continuity of care and unstable living conditions.  Conclusions: These results showed that the individualized protocol was effective for many but not all participants. Patients may have compounding factors that require additional interventions to supplement this protocol. This protocol is low cost to implement and adaptable to other clinical settings.